MANFAAT PARIWISATA DITINJAU DARI SOSIOLOGI HUKUM - Kurnia P Hutapea (Universitas Quality, 2019)
Humans as social beings (Zoon politicon) always need and love the other men in her life relationships that are mutually influencing, the instinct to always live together and the desire to blend with the surrounding natural atmosphere.Tourism is a form of travel to natural areas that is done with the aim of conserving the environment and preserve the life and well-being of local residents. Development and promotion of tourism when it is directed and planned properly, can help and preserve the environment, by introducing things - the original and the unit, clean, tidy and pleasant. The impact of tourism development can be positive as well as negative is the emergence of things - things we do not want and we can not refuse because it is - it is natural and normal.